Deregulated calcium signaling in blood cancer: Underlying mechanisms and therapeutic potential - Immanuel, Tracey; Li, Jixia; Green, Taryn N.; Bogdanova, Anna; Kalev-Zylinska, Maggie L. (Frontiers in Oncology, 2022)
Intracellular calcium signaling regulates diverse physiological and pathological processes. In solid tumors, changes to calcium channels and effectors via mutations or changes in expression affect all cancer hallmarks. Such changes often disrupt transport of calcium ions (Ca2+) in the endoplasmic reticulum (ER) or mitochondria, impacting apoptosis. Evidence rapidly accumulates that this is similar in blood cancer. Principles of intracellular Ca2+ signaling are outlined in the introduction. We describe different Ca2+-toolkit components and summarize the unique relationship between extracellular Ca2+ in the endosteal niche and hematopoietic stem cells. The foundational data on Ca2+ homeostasis in red blood cells is discussed, with the demonstration of changes in red blood cell disorders. This leads to the role of Ca2+ in neoplastic erythropoiesis. Then we expand onto the neoplastic impact of deregulated plasma membrane Ca2+ channels, ER Ca2+ channels, Ca2+ pumps and exchangers, as well as Ca2+ sensor and effector proteins across all types of hematologic neoplasms. This includes an overview of genetic variants in the Ca2+-toolkit encoding genes in lymphoid and myeloid cancers as recorded in publically available cancer databases. The data we compiled demonstrate that multiple Ca2+ homeostatic mechanisms and Ca2+ responsive pathways are altered in hematologic cancers. Some of these alterations may have genetic basis but this requires further investigation. Most changes in the Ca2+-toolkit do not appear to define/associate with specific disease entities but may influence disease grade, prognosis, treatment response, and certain complications. Further elucidation of the underlying mechanisms may lead to novel treatments, with the aim to tailor drugs to different patterns of deregulation. To our knowledge this is the first review of its type in the published literature. We hope that the evidence we compiled increases awareness of the calcium signaling deregulation in hematologic neoplasms and triggers more clinical studies to help advance this field.